Playing with Genre and Queer Narrative in the Novels of Malinda Lo - Alex Henderson (International Journal of Young Adult Literature, 2021)
Malinda Lo has been an invaluable voice in the emerging field of queer YA fiction, both for her accessible statistics on the representation of LGBTQIA+ identities in traditional publishing, and for the content of her novels. Her fictional works place sapphic protagonists into genre narratives – sci-fi, fairy tale, thriller – that are traditionally presumed to be the realm of straight heroes. But the queer rebellion in Lo’s writing goes beyond simply casting queer characters into genres and roles that have historically been considered heteronarrative: Lo’s work is an example of what I define here as ‘queer narrative play’, a process of deliberately and visibly troubling, tweaking, and upturning readers’ expectations of the roles and functions of queer characters within recognisable genre frameworks, deftly challenging the historical binary that has existed between ‘mainstream’ genre fiction and ‘marginal’ queer coming-of-age stories. Following from Tzvetan Todorov’s suggestion that “genres function as ‘horizons of expectation’”, this paper will explore how Lo’s body of work playfully challenges the traditional representation of LGBTQIA+ characters in a variety of methods; from creating speculative worlds that remove the need for narratives such as the coming-out story, to drawing readers’ attention to tragic queer tropes in order to make later subversions of them visible. Queer narrative play is an example of the ways in which contemporary YA writers may enact a rebellious conversation between author and reader, creating playful and progressive new works by reshaping the pre-existing materials of literary expectations, and Lo’s work makes for a stellar example of the craft.